PRoofster: Automated Formal Verification - Agrawal, Arpan; First, Emily; Kaufman, Zhanna; Reichel, Tom; Zhang, Shizhuo; Zhou, Timothy; Sanchez-Stern, Alex; Ringer, Talia; Brun, Yuriy (Proceedings (IEEE/ACM International Conference on Software Engineering Companion. Online), 2023)
Formal verification is an effective but extremely work-intensive method of improving software quality. Verifying the correctness of software systems often requires significantly more effort than implementing them in the first place, despite the existence of proof assistants, such as Coq, aiding the process. Recent work has aimed to fully automate the synthesis of formal verification proofs, but little tool support exists for practitioners. This paper presents oofster, a web-based tool aimed at assisting developers with the formal verification process via proof synthesis. oofster inputs a Coq theorem specifying a property of a software system and attempts to automatically synthesize a formal proof of the correctness of that property. When it is unable to produce a proof, oofster outputs the proof-space search tree its synthesis explored, which can guide the developer to provide a hint to enable oofster to synthesize the proof. oofster runs online at https://proofster.cs.umass.edu/ and a video demonstrating oofster is available at https://youtu.be/xQAi66IRfwI/.